KEMAMPUAN PENALARAN MATEMATIK SISWA MTs - Suharto, Mochamad Try; Chotimah, Siti (IKIP Siliwangi, 2018)
The reasoning is the ability to find a way to get the truth. In terminology, logic is the science that governs the process of human thinking so that the results presented can reach the truth. So it can be concluded also that by reasoning, humans can make an argument that is absolute and can be accepted by others through logical thinking. This research was conducted to determine the mathematical reasoning ability of MTs class 8 students on Triangle and Quadrilateral material based on indicators of mathematical reasoning ability that is to draw a logical conclusion and compose an argument, analogical reasoning, transductive reasoning, deductive reasoning, generalization and estimate answers, solutions or tendency with non-routine troubleshooting. The research method used is descriptive qualitative with data to be analyzed is qualitative data in the form of written and oral answers obtained from the written test. This research was conducted in MTs PPI 38 Padalarang with the subject of this research is class VIII-A which amounted to 31 people. Based on the results of research, students' mathematical reasoning abilities on MTs PPI 38 Padalarang are classified as sufficient. This is because there are some reasoning indicators that still need to be improved especially on analytical reasoning and generalization indicator as stated in the table which has been described.